Development of a multiphase photon Monte Carlo method for spray combustion and its application in high-pressure conditions. (December 2017) - Roy, Somesh P.; Cai, Jian; Modest, Michael F.
Highlights: A multiphase Monte Carlo radiation solver is developed for combustion simulations. The solver can handle both Eulerian & Lagrangian descriptions of the discrete phase. Nongray properties and semi-transparency affects radiation in Diesel sprays. Impact of radiation on spray evolution is negligible at high-pressure conditions. Multiphase radiation may have small effects on minor species in engine-relevant conditions. Abstract: In this work the development of a multiphase photon Monte Carlo (PMC) method with a focus on resolving radiative heat transfer in combustion simulations is presented. The multiphase PMC solver can account for description of participating media in both Lagrangian and Eulerian frameworks. The solver is validated against exact solutions in several one-dimensional configurations. The developed solver is then applied to Diesel spray combustions, where liquid spray droplets are assumed to be cold, nonemitting, large, and isotropically scattering. Several formulations for radiative properties of the Diesel spray are first explored. The PMC solver has then been coupled with the multiphase spray combustion solver in OpenFOAM and the coupled solver is used for simulations of high pressure Diesel spray combustion. It was found that in typical Diesel spray combustion applications, such as in an internal combustion engine, impact of radiation on the evolution of the liquid spray was insignificant. Although the impact of radiation on the spray was minimal, nongray spectral properties and the assumption of semi-transparency for Diesel spray were found to impact the radiative transfer significantly, while impact of scattering was marginal. Spray radiation was also found not to have much effect on global combustion characteristics in high-pressure engine-relevant configurations. However, a small but noticeable effect on minor species distribution relevant to pollutant formation was observed.